Experimental and theoretical evidence for temperature driving an electric-magnetic complementary effect in magnetic microwave absorbing materials. Issue 5 (29th January 2020) - Yang, Xuan; Duan, Yuping; Zeng, Yuansong; Pang, Huifang; Ma, Guojia; Dai, Xuhao
Abstract : Magnetic microwave absorbing materials (MMAMs) possess many desirable properties, including thin thickness and wide attenuation band, and thus are widely applied in many fields. Abstract : Magnetic microwave absorbing materials (MMAMs) possess many desirable properties, including thin thickness and wide attenuation band, and thus are widely applied in many fields. However, the mechanisms of variation in performance of MMAMs at dynamic temperature are difficult to characterize and poorly understood. In this work, we combine experiments and fluctuation-induced tunneling (FIT) simulations to delineate the effects of temperature on the microwave absorption properties of MMAMs. We find that the increase in temperature weakens the complex permeability of the carbonyl iron particles (CIPs)/epoxy coating, while also strengthening the complex permittivity. FIT simulations explain the experimental observations by showing that the tunneling current between two CIPs with a gap of a few nanometers increases with increasing temperature. Furthermore, crescendo conductance loss and decrescendo magnetic loss form an electric-magnetic complementary effect, so that the coating exhibits superior microwave absorption performance (maximum effective bandwidth 8 GHz) in the temperature range of 293 K–573 K, a result with implications for the broad understanding and design of MMAMs applied at high temperatures.